Stimulation of human bone marrow mesenchymal stem cells by electromagnetic transduction therapy - EMTT. (3rd July 2022) - Gerdesmeyer, Ludger; Zielhardt, Paula; Klüter, Tim; Gollwitzer, Hans; Gerdesmeyer, Lennart; Hausdorf, Joerg; Ringeisen, Martin; Knobloch, Karsten; Saxena, Amol; Krath, André
ABSTRACT: Many different pulsed electromagnetic field (PEMF) devises have been clinically used to stimulate healing processes, but many procedures are still without supporting basic research data. The aim of this study was to investigate a new modified pulsed electromagnetic field therapy: electromagnetic transduction therapy (EMTT). EMTT is technically based on high-intensive PEMFs with a magnetic field strength between 80 and 150 mT. The effect of EMTT for a 10-min session three times a week on human bone marrow mesenchymal stem cells (MSCs) was evaluated by assessing cell viability, gene expression of bone regenerative factors and VEGF-A (vascular endothelial growth factor) secretion after 7 and 14 days of treatment. No negative or toxic effects of EMTT on MSCs in vitro were observed in the applied test frame. The VEGF-ELISA at day 7 of EMTT treatment with 80 mT showed a significant higher VEGF concentration compared to untreated control group. In conclusion, high-intensive electromagnetic impulses showed no harmful effects on MSC cultures in our study. The enhancement of the proangiogenic factor VEGF in MSCs on day 7 indicates a substantial role in cell-stimulating effect of EMTT. Further in vitro and in vivo studies should differentiate specific stimulating and regenerating effects of EMTT impulses in soft tissue engineering. Specific electromagnetic characteristics have to be determined to optimize electromagnetic treatment options in orthopedic surgery and traumatology and soft tissue treatment options.